Refractive index retrievals for polystyrene latex spheres in the spectral range 220-420 nm - Galpin, Tyler; Chartier, Ryan T.; Levergood, Nicholas; Greenslade, Margaret E. (Aerosol science and technology, 2017)
The recent development of an Aerosol Extinction Differential Optical Absorption Spectrometer (AE-DOAS) has allowed for the retrieval of wavelength dependent complex refractive indices for polystyrene latex spheres (PSL). The AE-DOAS is a white-type multi-pass gas cell coupled to a UV-Vis spectrometer. Refractive index values are retrieved for wavelengths between 220 and 420 nm by minimizing the χ 2 goodness-of-fit between measured extinction for five diameters of PSL and model Mie Theory predictions. Comparison to literature shows agreement at wavelengths >360 nm demonstrating the validity of this new instrumental approach while expanding the known refractive index range for PSLs further into the UV where it is previously unreported. In the studied wavelength range, coefficients for the general Cauchy dispersion relationship (A = 1.538(11); B = 0.0043(16) μm 2 ; C = 0.00094(5) μm 4 ) for PSLs were determined using the retrieved real portion of the refractive index and the wavelength in microns. In addition, this work indicates that the precision of retrieved values is impacted by the particle diameters chosen for the experiment where retrievals for shorter wavelengths of light benefit from the study of smaller sized particles. Copyright © 2017 American Association for Aerosol Research